A Compact MultiBand and Dual-Polarized Mobile Base-Station Antenna Using Optimal Array Structure - Young-Bae Jung; Soon-Young Eom (International Journal of Antennas and Propagation)
This paper introduces a multiband base-station antenna to provide multiple communications services. There is growing need for multiband base-station antennas for mobile communications to serve existing 2nd and 3rd generation systems and to provide emerging 4th generation communication service as well as WiFi. For example, cellular, PCS, and especially WCDMA service are currently widely used in Korea, and 4th generation service (WiBro and LTE), introduced in 2011, will have to operate in parallel with existing services. The proposed multiband base-station antenna can provide a single/dual/triple or more multiple services using dual-polarization (±45° linear polarizations) according to the requirements of the service provider. This antenna has a shared aperture, having several array antenna sets for multiple services (Band 1: cellular service in 0.824~0.894 GHz, Band 2: PCS, WCDMA, and WiFi in 1.920~2.170 GHz, Band 3: WiBro and WiMAX in 2.300~2.400 GHz, and Band 4: WiMAX in 5.150~5.850 GHz). This antenna can be helpful for reducing base-station operating expenses and to create a clean urban landscape by minimizing the number of base-station antennas, which are increasing rapidly.